Microplastics in Sediment of Kuakata Beach, Bangladesh: Occurrence, Spatial Distribution, and Risk Assessment - Banik, Partho; Hossain, M. Belal; Nur, As-Ad Ujjaman; Choudhury, Tasrina Rabia; Liba, Samia Islam; Yu, Jimmy; Noman, Md. Abu; Sun, Jun (Frontiers in Marine Science, 2022)
Kuakata beach, known as Daughter of Sea in Bangladesh, has drawn a growing number of tourists from all over the world, leading to the higher use of single plastic products. This study was a first attempt to describe the occurrence, spatial distribution, and ecological risk of microplastics (MPs) in Kuakata beach sediments. A total of 24 surface sediment samples were collected from the intertidal zone of the beach, and MPs were extracted using the density separation method and a stereomicroscope. Fourier transform infrared (FTIR) spectroscopy was used for qualitative and quantitative identification. The results revealed that the average MPs in the beach sediment were 232 ± 52 items kg–1 dry weight, which was much higher than many other sandy beaches throughout the world. Analyses of variance showed a significant (p < 0.01) difference among the mean abundance of MPs in sampling points. Fibers were dominated in every sampling point with an average of 123 ± 27 item kg–1. Most of the MPs observed were colored (60%), and the rest were transparent (40%). It was found that the size range of 1–5 mm MPs constituted over half (55%) of total MPs covering an average value of 127 ± 34 items kg–1. Three polymer types were identified in the sediment samples through FTIR analysis which followed the decreasing order of polyethylene terephthalate > polyethylene > polypropylene. Correlation analysis showed a positive relationship between the abundance of MPs and the finer grain size of sediment (p = 0.055; r = 0.7), indicating grain size-controlled the density of MPs. The pollution load index was assessed to estimate the ecological risk and found that the beach sediment of Kuakata belonged to the risk category I of the pollution index. This investigation provided preliminary information on MPs pollution in the marine ecosystem that the policymakers can use to take appropriate management approaches.